O uso de jogos na sala de aula para dar significado ao conceito de números inteiros - Neves, Renato Silva (Universidade Federal de São Carlos, 2010)
This work was elaborated from the research on a well-known epistemological obstacle: the difficulty that the students have in understanding the concept of negative number and operations with such numbers. The experience in the classroom shows that this difficulty is indeed wide. To investigate the causes and methods to overcome such obstacles to contribute to the development of studies related to the understanding of the rules of signs of integers, four didactic games were applied: the Activity of Positive and Negative Cards, the Dinosaur s Game, the Hexagon Game and the Matix Game. This work evaluated in which aspects these four didactic games help the teacher to develop a meaningful learning, in addition to improve the performance of creativity, spontaneity and autonomy of learners. As the final product of this Professional Master's Degree, the activities developed were posted on the Professor s Portal created by the Ministry of Education and available on: http://www.portaldoprofessor.mec.gov.br, a virtual environment with educational resources which stimulate and facilitate the work of teachers. Thus, it tried to offer some contribution to studies related to mathematics didactic games with the suggestion of these activities for Primary School.
Keywords: Matemática - estudo e ensino; Números inteiros; Jogos educativos; Jogos; Números inteiros; Games; Numbers; CIENCIAS EXATAS E DA TERRA::MATEMATICA